Colombia : Staff Report for the 2001 Article TV Consultation and Second Review Under the Extended Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Colombia's economic performance deteriorated markedly in 1998-99 owing to a combination of external shocks. The main program objectives for 2001 are to achieve a further reduction in inflation to 8 percent, continue the recovery of economic activity, and strengthen the public finances further to support the expansion of activity in the private sector. The structural reform agenda for 2001 calls for considerable action to strengthen the control over expenditure at all levels of the public sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet